Sinais radiográficos da densidade mineral óssea em radiografias panorâmicas de pacientes pré e pós-menopausa - Faria, Paula Cristina de [UNESP]; Villaça-Carvalho, Maria Fernanda Lima [UNESP]; Lopes, Sérgio Lúcio Pereira de Castro [UNESP]; Moraes, Mari Eli Leonelli de [UNESP]; Manhães Júnior, Luiz Roberto Coutinho [UNESP] (Editora Cubo, 2017)
Objective: The aim of this study was to evaluate the potential of panoramic radiographs (PR) and their radiomorphometric indices as an auxiliary method for the diagnosis of osteoporosis. Material and Methods: Twenty five women were selected, who had been prescribed PR for different purposes. The PR were analysed according to the MCI, which evaluates the mandibular cortex below the mental foramen, and then divided into two groups: normal and bone mineral loss. Bone densitometry scans were obtained (DXA) from the lumbar spine and neck of the femur/whole femur, which were used as the gold standard for comparison against the MCI. Kappa test (p<0.05) was used to determine the association between the MCI and bone densitometry readings. Results: Regarding the DXA, 7 patients were normal at the lumbar spine or femur, 24 subjects showed osteopenia at the lumbar spine or femur and 9 subjects had osteoporosis at the lumbar spine or femur. Regarding the association between DXA and MCI, 18 subjects showed some degree of bone loss at the spine detected by both DXA and the Klemetti index. Conclusions: PR should not be used to confirm the diagnosis of osteoporosis or osteopenia, but may be useful to assess the risk of such diseases being present.
Radiographic signs of bone mineral density in panoramic radiographs from pre and postmenopausal patients
Keywords: Menopause; Osteoporosis; Panoramic radiography